FIGURATIVE LANGUAGE USED IN THE GREATEST SHOWMAN SOUNDTRACK LYRICS - Natalia Marpaung; Madina Madina; Afrida Fitri Yani Sipahutar (Jurnal Basataka (JBT), 2022)
This study is entitled Figurative Language Used In The Greatest Showman Soundtrack  Lyrics.This study aims to analyze figurative language or figurative language in four songs which are the soundtrack of the film The Greatest Showman, in which the four songs are titled, Never  Enough, This Is Me, and A million Dream.The benefits of this research are divided into two, namely: theoretically this research aims to help become a reference for other researchers, and the second is the benefits for students, namely to increase students' understanding of language style and to help improve students' literacy skills. This study uses a descriptive qualitative approach with literature study techniques. The results of the research are that there are five styles of language in the song above, namely: personification (1.2%), metaphor (1.2%), hyperbole (2.4%), imagery (0.2%), and repetitive (1.4%).